USAHA PENINGKATAN KOMPETENSI SOFTSKILL MELALUI STUDENT CENTERED-LEARNING BAGI MAHASISWA YANG MENGIKUTI MATA KULIAH ANALISA PERANCANGAN SISTEM - Rifiana Arief (Jurnal Pendidikan Teknologi dan Kejuruan, 2012)
ABSTRACTThe face to face learning process focuses on teacher-centered learning (the center of the learning activityis on the teacher or lecturer – the students just notice and listen the lecturer’s explanation), it is the reverse ofstudent-centered learning (students’ active participation). The changing of learning model from teacher-centeredapproach into student-learning center should be conducted to increase the students’ active participation in SystemDesign and Analysis course. The research methods to improve students’ softskills competency through studentcentredlearning were (a) making lecturer team who taught System Design and Analysis course (b) reviewingthe syllabus of lecturing unit (c) developing a learning model of student learning center to maximize the students’hardskills and to stimulate their softskills (d) conducting socialization of new revised syllabus of lecturing unitthat covered softskills competency, of which it had been validated by the university party (e) implementing thelearning process with the student-learning center approach by using syllabus of System Design and Analysiswhich covered softskills competency. By implementing the model of student learning center on System Design andAnalysis learning process, it was expected to be able to maximize the understanding of hardskills, technology foranalysis and information system design as well as to stimulate the student’s intrapersonal and interpersonal skills(softskills), who completed the course.Keywords: softskills competency, student-centred learning, System Design and Analysis,